The Effect of Green Marketing Mix on Tupperware Purchasing Decisions in Yogyakarta City - Khonifah, Febbiyana; Harsoyo, Titik (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to analyze the influence of the green marketing mix on purchasing decisions for Tupperware products in the city of Yogyakarta. The independent variables used in this study are Green Product, Green Price, Green Place, and Green Promotion, while the dependent variable is purchasing decisions. Employing a causal quantitative approach, data collection involved distributing questionnaires to 100 respondents who had previously purchased Tupperware products in Yogyakarta. The questionnaire items for all variables were validated and proven reliable. Classical assumption tests demonstrated normally distributed data, a regression model without multicollinearity, and no occurrence of heteroscedasticity. The research findings indicate that Green Product, Green Place, and Green Promotion have positive and significant effects on purchasing decisions. However, Green Price does not exhibit a positive and significant impact on purchasing decisions. These results provide valuable insights into the factors influencing consumers' decisions to purchase Tupperware products with a focus on the green marketing mix elements.